Declarations and the Indonesian Constitution on Religious Freedom - Binawan, Alexius Andang L. (Al-Jamiah Research Centre, 2011)
One of controversial issues in Indonesia regarding human rights is concerning religious freedom. There were two contradict opinions on the issue, i.e. those who preferred Indonesia as an Islamic state, with a consequence that there is only very limited religious freedom and those who preferred secular state with a wider religious freedom. Though finally Indonesia adopted Pancasila (five pillars) as the state ideology, as a mid-way between the two, final agreement on the problem is from being finalised as debates are still carried out. This paper is aimed at analysing how and where the âpendulumâ is swinging between two contrasting views since Indonesia has signed both the International Covenant on Civil and Political Rights and also the Cairo Declaration of Human Rights. I argue that during the New Order Indonesia, the pendulum on religious freedom swung closer to Islamic view.[Salah satu isu terkait Hak Asasi Manusia di Indonesia adalah mengenai kebebasan agama. Setidaknya ada dua cara pandang yang saling bertentangan, yaitu (1) yang menghendaki bentuk negara Islam, konsekuensinya adalah kebebasan agama sangatlah terbatas, dan (2) yang menginginkan negara sekuler yang mengindikasikan kebebasan agama lebih luas. Indonesia mengadopsi Pancasila sebagai ideologi negara dan sebagai jalan tengah antara kubu negara Islam dan sekuler, namun perdebatan mengenai bentuk negara tersebut terus saja bergulir. Artikel ini menganalisis bagaimana dan ke mana âpendulumâ bergerak di antara dua pandangan yang saling bertentangan di atas. Semasa Orde Baru, pendulum tersebut condong ke kubu Islam.]